PENGARUH KUALITAS LAYANAN DAN KEMUDAHAN PENGGUNAAN TERHADAP KEPUASAN NASABAH APLIKASI TRING BY PEGADAIAN STUDI PADA PEGADAIAN SYARIAH CABANG PASAR NGABUL - Awaliha Ainun; Dian Pujiatma Vera Subchanifa (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyze the influence of service quality and ease of use of the TRING by Pegadaian application on customer satisfaction at the Pegadaian Syariah Pasar Ngabul Branch using a quantitative approach based on the Technology Acceptance Model (TAM). Data were collected from 100 respondents through a structured questionnaire using a Likert scale and analyzed using SPSS software. The analytical techniques included validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results show that service quality and ease of use individually have a positive and significant effect on customer satisfaction. Simultaneously, both variables also significantly influence customer satisfaction. Among the two variables, ease of use has a more dominant effect than service quality. The findings indicate that the research model explains a substan tial proportion of customer satisfaction, highlighting the importance of user-friendly digital services and quality service delivery in improving customer satisfaction and supporting digital transformation in Islamic pawnshop services.